Prevalencia y factores de riesgo de ictericia neonatal en el servicio de neonatología del Hospital Regional de Loreto 2018 – 2020 - Pasquel Silva, David Romario (2025)
Introduction Neonatal jaundice is clinically evidenced by yellowish skin and mucous membranes, and is predominantly indirect bilirubin and this occurs in term or preterm infants, whose prevalence is among the top ten causes of morbidity in the newborn, which They will need inpatient care in the neonatal services for their management. Goal To identify the prevalence and risk factors of Neonatal Jaundice in the neonatology service of the Regional Hospital of Loreto between 2018-2020. Methodology An observational, analytical and retrospective study of cases and controls will be applied through the information of newborns admitted to the Neonatology Service of the Regional Hospital of Loreto from 2018 to 2020. Obtained the approval of the research project and a request will be made for the permission and evaluation of the Research Committee and Ethics Committee of the Regional Hospital of Loreto "Felipe Santiago Arriola Iglesias"; Primary sources will be used, the data of neonates with the diagnosis of neonatal jaundice will be obtained. Results: When said research project is carried out Recommendations: Improve strategies for the timely diagnosis of neonatal jaundice, which need attention for its management and thus avoid complications. Plan and execute similar research studies.